Modeling of degradation processes in concrete: Probabilistic lifetime and load-bearing capacity assessment of existing reinforced concrete bridges. (15th July 2016) - Šomodíková, Martina; Lehký, David; Doležel, Jiří; Novák, Drahomír
Highlights: The methodology of probabilistic assessment of existing bridges is introduced. The assessment takes into account the deterioration level of the building materials. Time-dependent analysis of the existing girder bridge is performed. Information for decision making about maintenance or repairs of bridges are obtained. The proposed methodology can be generally used for any type of the structure. Abstract: A large number of old bridges are to be found on highways and roads all around the world. Considering their age and deterioration level, many of them need to be reconstructed. However, in the majority of cases, the load-bearing capacity of such bridges is just reduced to take account of their current state in spite of the fact that these structures continue to deteriorate. Their detailed reliability and lifetime assessment should therefore be a primary goal. Advanced methods of reliability analysis in combination with nonlinear finite element method-based analysis represent effective tools for the assessment of existing bridges. Data regarding the current level of load-bearing capacity and its expected development in the coming years (and whether or not the required level of reliability will be met) may help in the systematic scheduling of bridge maintenance and/or facilitate decision making about the effective reconstruction of the structure. This paper introduces a method for the probabilistic determination of the load-bearing capacity of bridges with respect to the progression of ongoing degradation processes over time. The method is used to determine the current load-bearing capacity of a 60-year-old reinforced concrete bridge, and for its estimation in the coming years until the end of the theoretical service life of the structure.